High performance asymmetric supercapacitor based on CoAl-LDH/GF and activated carbon from expanded graphite. Issue 52 (12th May 2016) - Masikhwa, Tshifhiwa M.; Madito, Moshawe J.; Momodu, Damilola Y.; Dangbegnon, Julien K.; Guellati, Ouanassa; Harat, Aicha; Guerioune, Mohamed; Barzegar, Farshad; Manyala, Ncholu
Abstract : An asymmetric supercapacitor based on CoAl-LDH/GF composite and activated carbon from expanded graphite (AEG) in aqueous 6 M KOH electrolyte is reported with excellent electrochemical properties. Abstract : An asymmetric supercapacitor fabricated with a CoAl-layered double hydroxide/graphene foam (LDH/GF) composite as the positive electrode and activated carbon derived from expanded graphite (AEG) as the negative electrode in aqueous 6 M KOH electrolyte is reported. This CoAl-LDH/GF//AEG cell achieved a specific capacitance of 101.4 F g −1 at a current density of 0.5 A g −1 with a maximum energy density as high as 28 W h kg −1 and a power density of 1420 W kg −1 . Furthermore, the supercapacitor also exhibited an excellent cycling stability with ∼100% capacitance retention after 5000 charging–discharging cycles at a current density of 2 A g −1 . The results obtained show the potential use of the CoAl-LDH/GF//AEG material as a suitable electrode for enhanced energy storage in supercapacitors.